Is demonetisation a demon for Indian tourism industry?. (July 2017) - Ohlan, Ramphul
Abstract: In this paper, the crucial issue we seek to address is whether India's sudden demonetisation has a significant influence on its international tourist arrivals. We do so by investigating the stationary characteristics of monthly data of foreign tourist arrivals to India over the period 2003 to 2017 using recently developed break-point unit root tests. We find that the series of tourist arrivals to India is stationary and the impact of shocks is neutral. In addition, no significant structural break in tourist arrivals to India is associated with sudden demonetisation. These findings highlight the resilience of Indian tourism industry to the shock of demonetisation. Therefore, it is suggested that the Government of India should continue to pursue its long-term strategy to attract foreign tourist arrivals. Highlights: The significance of influence of shocks on number of foreign tourist arrivals is tested. Newly developed break-point unit root tests are used. The influence of shocks on Indian tourism industry is temporary. India should continue to pursue its long-term strategy to attract foreign tourist arrivals.